2019
DOI: 10.1097/cm9.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhubarb on the expression of glucocorticoids receptor and regulation of cellular immunity in burn-induced septic rats

Abstract: Background: It is important to modulate the expression of glucocorticoids receptor (GR) in tress and maintain the immunity homeostasis in sepsis process. Rhubarb have been shown to have potential effects on anti-inflammatory and immune modulation. The present study was designed to investigate the effects of rhubarb on the expression of GR and cellular immunity in burn-induced septic rats. Methods: Sixty-six healthy male Sprague Dawley (SD) rats were randomized into seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…e main difference between CA and TA groups was the presence of Rhubarb. ese results were in line with a previous report and suggested that Rhubarb may play a vital role in burn wound healing [4].…”
Section: Inflammatory Cytokine Immunoassaysupporting
confidence: 93%
See 1 more Smart Citation
“…e main difference between CA and TA groups was the presence of Rhubarb. ese results were in line with a previous report and suggested that Rhubarb may play a vital role in burn wound healing [4].…”
Section: Inflammatory Cytokine Immunoassaysupporting
confidence: 93%
“…Rhubarb, Scutellaria root, Phellodendron bark, and Coptidis rhizome are the four most frequently used materials to prepare "San Huang Powder." Moreover, Rhubarb's efficacy in treating burn wounds was recently reported [4,5]. However, there is no systematic study comparing the efficacy of different "San Huang Powder" recipes for the treatment of burn wounds to date.…”
Section: Introductionmentioning
confidence: 99%
“…Septic mice had significantly improved 7-day survival and reduced acute organ injury, which is associated with stimulated IL-10+ Foxp3+ Tregs, inhibited Th17 differentiation, and decreased Th17/Tregs (104). Some TCM, such as rhubarb, have a bidirectional regulatory effect on the heterogeneity of Tregs over time and improve the prognosis of sepsis by increasing the proportion of Tregs in the early stage and decreasing it in the late stage, although the specific molecular mechanism of their effect is not clear (100). Although these results are contradictory, they do imply that Foxp3+ Tregs play an important role in amending early, late, and even long-term immune disturbances after sepsis.…”
Section: Time-dependent Treg Patterns In Sepsismentioning
confidence: 99%
“…Due to their relatively stable genetic uniformity, inbred BALB/c and C57BL/6 mice are most frequently used in sepsisrelated studies (47,59,65,70,83,86,98,118,177). Nevertheless, researchers are beginning to emphasize the importance of using genetically heterogeneous organisms in experiments since they can better simulate the heterozygosity of humans, especially in multi-dimensional heterogeneous syndromes such as sepsis (19,23,67,85,100,135,136). BALB/c (inbred) and CD-1 (outbred) mice underwent unilateral femoral fracture, splenectomy, and hemorrhagic shock, with increased circulating granulocytes (LY6G+CD11+) in both strains at 24 and 48 hours later.…”
Section: Limitations Of Treg Models In Sepsismentioning
confidence: 99%
“…ex Balf. Rheum palmatum L. is a valuable medicinal plant widely distributed in the alpine and desert regions of Asia and Europe. It has anti-inflammatory, antiviral, antipyretic, antitumor, and other biological activities. , According to Chinese medicine textbooks published by the Ministry of Education of China, most ischemic stroke types can be classified as heat syndromes, such as a decrease in qi and blood and an increase in wind and fire. Therefore, traditional Chinese medicines that reduce excess heat and purify fire are often used to treat ischemic stroke, such as R.…”
Section: Introductionmentioning
confidence: 99%